RESEPSI MAHASISWA JURNALISTIK TERHADAP DRAMA KOREA THE WORLD OF THE MARRIED COUPLE (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This type of research uses a qualitative approach, with a reception analysis method, with Stuart Hall's encoding-decoding model. Meanwhile, the informants in this study were students majoring in journalism at UIN Alauddin Makassar, who watched from the beginning to the end of the drama The World of The Married Couple. Then explain their interpretation through in-depth interviews, and get reception from all the informants. The results found from this study indicate that the receptions of journalistic students towards the Korean Drama The World of The Married Couple are almost the same. According to the knowledge of each respondent who has been interviewed, their understanding and meaning show that a strong message in this drama is that Sun Woo is cast as a strong and independent woman. In the three positions the dominant hegemony, negotiation and opposition. Respondents gave their affirmation, from the three sets of Stuart Hall's theory above, several main points can be drawn, namely, negative stereotypes, women's resistance, women as victims of infidelity, women's independence, recognition of negative attitudes made by men with imagination related to sexual fantasies. In the decoding process, researchers have described the five informants based on Stuart Hall's theory, namely the dominant hegemonic position. Of the five informants who have been interviewed in positions of dominant hegemony, they received a message in this drama that women who are hurt (cheated on) will not always be weak. The social discrimination that women are always under the shade of men has been proven by Sun Woo's character, the stereotype about weak women is not true.